2001
DOI: 10.1126/science.1063414
|View full text |Cite
|
Sign up to set email alerts
|

A Cortical Area Selective for Visual Processing of the Human Body

Abstract: Despite extensive evidence for regions of human visual cortex that respond selectively to faces, few studies have considered the cortical representation of the appearance of the rest of the human body. We present a series of functional magnetic resonance imaging (fMRI) studies revealing substantial evidence for a distinct cortical region in humans that responds selectively to images of the human body, as compared with a wide range of control stimuli. This region was found in the lateral occipitotemporal cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

127
1,404
11
10

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,842 publications
(1,552 citation statements)
references
References 21 publications
127
1,404
11
10
Order By: Relevance
“…4; Table I). LOTC clusters probably intersected the human motion complex (V5/hMT+) and/or extrastriate body area [EBA; Downing et al, 2001; particularly its hand representation; Orlov et al, 2010]. This is in line with previous results, showing LOTC to carry information about observed manual actions [Oosterhof et al, 2012b] and extends them to motor imagery.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…4; Table I). LOTC clusters probably intersected the human motion complex (V5/hMT+) and/or extrastriate body area [EBA; Downing et al, 2001; particularly its hand representation; Orlov et al, 2010]. This is in line with previous results, showing LOTC to carry information about observed manual actions [Oosterhof et al, 2012b] and extends them to motor imagery.…”
Section: Discussionsupporting
confidence: 84%
“…This analysis confirmed that imagined hand actions could be decoded from activity patterns in left M1 and PMC, as well as right SPL (with one significant cluster in the left precentral gyrus, two in the left SMA, and one in right SPL). In addition, the searchlight analysis revealed significant clusters in right motor cortices (two stretching across pre‐ and postcentral gyrus, one in the SMA) and bilateral early visual cortex (EVC; two in the right hemisphere and one large cluster stretching from left EVC to left SPL), as well as bilateral human motion complex (V5/hMT+) and/or the extrastriate body area (EBA; left and right cluster stretching into fusiform gyrus and IPL, respectively; left peak coordinates being very close to EBA coordinates reported by Downing et al [2001]). See Figure 4 and Table 1 for a summary and peak coordinates of all clusters.…”
Section: Resultssupporting
confidence: 77%
“…In particular, extrastriate body area (EBA) located at the posterior inferior temporal sulcus/middle temporal gyrus (Downing et al, 2001) and the fusiform body area located at the ventro-medial temporal cortex (Peelen & Downing, 2007) display a highly selective activity for visual presentations of human bodies. These areas respond selectively to photorealistic depictions of whole human bodies or body parts, still images of human bodies or body parts extending to 'stick figures' and silhouettes, in preference to human faces, images of object parts and scenes (Downing et al, 2004;2006;Peelen & Downing, 2007;Urgesi, Berlucchi & Aglioti, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was based both on neuroimaging studies of reading and on anatomo-clinical correlations in patients with pure alexia, an acquired deficit of reading that follows left occipitotemporal lesions (McCandliss et al, 2003). The VWFA hypothesis was framed in the broader context of recent studies of functional specialization within the human ventral visual stream, in which have been identified several areas specialized for other classes of visual stimuli such as faces, places, or body parts (Downing et al, 2001;Hasson et al, 2003;Haxby et al, 2001;Kanwisher et al, 1997).…”
Section: Introductionmentioning
confidence: 99%